Deciphering Obstructive Sleep Apnoea Syndrome: A Clinical Profile Analysis of Patients in a Tertiary Care Hospital in Eastern Nepal - Bhatta, Karuna; Ghimire, RamHari; Kayastha, Jyoti; Mishra, Navin Kumar; Shrestha, Sareen; Chand, Hema (Nepalese Respiratory Journal, 2025)
Background: Obstructive Sleep Apnoea Syndrome (OSAS) is a common disorder comprising repeated events of partial or complete obstruction of the upper airway during sleep, thereby disturbing sleep and other physiological events and leading to long-term consequences. The condition is often left underdiagnosed, particularly in regions like Eastern Nepal, where awareness and access to diagnostic tools are limited. Objective: This paper will examine the clinical profile of OSA in the eastern region of Nepal, focusing on its risk factors and associated comorbidities. Methods: This study was conducted as a hospital-based descriptive cross-sectional study at Nobel Medical College and Teaching Hospital from November 2023 to November 2024. A sample of thirty adults diagnosed with OSA by polysomnography (PSG) according to American Academy of Sleep Medicine diagnostic criteria were included. Patients with untreated OSAS were included; those with respiratory failure, heart failure, shock, and recent ICU admission were excluded. Data regarding demographics, risk factors, co morbidities, spirometry, and PSG data were collected and analyzed with SPSS version 25. Results: A total of 30 OSA patients were enrolled in the study, comprising 20 males (66.7%) and 10 females (33.3%). The mean age was 54.07 years, with the 40–60 age group being the most common. Among the participants, 14 (46.7%) had mild OSA, 11 (36.7%) had moderate OSA, and 5 (16.7%) had severe OSA. Additionally, 7 patients (23.3%) had hypertension, and 4 (13.3%) had diabetes. Regarding spirometry findings, restrictive patterns (46.7%) were predominant among patients, followed by obstructive patterns (20%) and normal findings (33.3%). Conclusion: OSA is a complex, multifactorial disease with distinct phenotypes commonly prevalent among the Nepalese population, which needs early diagnosis and proper treatment. OSA evaluation should comprise both sleep-related complaints and nonspecific symptoms simultaneously.